Implementasi Game Wordwall di Madrasah Ibtidaiyah untuk Menciptakan Lingkungan Kelas yang Interaktif - Anisa Yulia Saputri; Nurul Layli (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
The limited use of game-based learning media at the Madrasah Ibtidaiyah (MI) level poses a significant challenge to creating meaningful, enjoyable learning experiences and interactive classroom environments. This study employs a literature review method to examine how the implementation of WordWall as a game-based learning tool can foster an interactive classroom environment. Data were gathered by analyzing various articles and journals relevant to the topic. The findings indicate that the WordWall platform effectively boosts student interest, enthusiasm, and active participation in both group and individual learning activities, while also serving as a tool for assessing student comprehension. Optimal results from this implementation depend on the availability of supporting facilities and the teacher's proficiency in operating the platform and utilizing its features including managing situations where network disruptions occur. However, to prevent student boredom resulting from repetitive use of the same medium, teachers should strive for creativity by integrating WordWall with a variety of other learning media and methods.